Increased C1q binding and arthritis in primary biliary cirrhosis. Issue 5 (May 1980) - Crowe, J P; Molloy, M G; Wells, I; Thompson, B R; Holborow, E J; Hamilton, E; Williams, R
Abstract : Using the C1q binding assay, circulating immune complexes were detected in 31 of 50 (62%) patients with primary biliary cirrhosis and 17 of these had arthritis. This took the form of a seropositive inflammatory polyarthritis in 12 of 18 patients with C1q binding greater than or equal to 20%, whereas a milder seronegative arthritis associated with scleroderma and Raynaud's phenomenon was found in five of 13 patients with C1q binding < 20%. Only two of the 19 patients with normal binding had arthritis and this was of a mild and transient nature. There was a positive correlation between C1q binding and the serum concentrations of IgG and IgM. Results also supported the hypothesis that circulating immune complexes may be involved in the development of arthritis in patients with primary biliary cirrhosis.